Comparison of Orthogonal Transforms for OFDM Communication System - Aboltins, A. (Elektronika ir Elektrotechnika, 2011)
Classical orthogonal frequency division (OFDM) employs fast Fourier transform (FFT) for elimination of inter-symbol interference (ISI) and expansion of time support of the transmitted signals. However FFT could not always be optimal in terms bit error ratio (BER) due channel variations, Doppler Effect, nonlinearities and high peak-to-average power ratio of the signal. Aim of this publication is to experimentally compare different orthogonal transforms and outline impact of these transforms on BER of the communication system with noisy, frequency selective and nonlinear communication channels. Simulation results of OFDM communication systems with equalization and no transform, with FFT, Hadamard and Generalized nonsinusoidal orthogonal transforms are presented. Ill. 5, bibl. 9, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.361